Yield gap management under seawater intrusion areas of Indonesia to improve rice productivity and resilience to climate change - Sembiring, Hasil; Subekti, N.A.; Erythrina; Nugraha, Dedi; Priatmojo, Bhakti; Stuart, Alexander M. (MDPI, 2019)
The purpose of this study was to evaluate (a) the performance of two modern rice varieties (non-tolerant and tolerant for saline soils) under different fertilizer management options, and (b) assess the yield gap and income increase through proper crop and nutrient management at different levels of soil salinity. Experiments were carried out in moderate and high levels of soil salinity in West Java, Indonesia. A split plot design with three replications was used. The main plots included two rice varieties, Inpari-30 Ciherang sub1 and Inpari-34 (tolerant variety for saline soils), and subplots included eight fertilizer management treatments. Farmer participatory field trials were also established across three levels of soil salinity with four different rice varieties, Sidenuk, Inpari 30, Inpari 34, and Inpari 35, and a fertilizer package consisting of organic and inorganic fertilizers. Under low and moderate soil salinities, Sidenuk and Inpari 30 with recommended practice had higher productivity and economic benefit compared to the saline tolerant rice varieties, Inpari 34 and Inpari 35. However, under high soil salinity, the yields of Inpari 34 and Inpari 35 with recommended practice were 93% higher than farmers’ practice, representing an exploitable yield gap of 1.3 t ha−1 and benefit above fertilizer cost of USD 301 ha−1. The combination of tolerant varieties and improved nutrient management use for rice production can therefore be used as a strategy for improving farmers’ income and livelihoods in coastal areas of Indonesia.